A study on elastic properties of carbon nanocones based on a temperature-related quasi-continuum model. Issue 8 (3rd August 2017) - Wang, Xiaojing; Wang, Xiangyang; Qi, Huibo; Song, Xiushu; Li, Runze
ABSTRACT: In the present paper, general analytical formulas for calculating the Young's modulus and Poisson's ratio of single-walled carbon nanocones (SWCNCs) at finite temperatures are derived based on the proposed temperature-related multiscale quasi-continuum (QC) model. To this end, a temperature-related higher-order Cauchy-Born (THCB) rule is employed to establish the hyper-elastic constitutive model of SWCNCs. With use of the proposed approach, the influences of the temperature, apex angle, rotation angle of cutting lines and top end radius on the Young's moduli and Poisson's ratios of SWCNCs are investigated systematically.